Comparison of Single Axillary vs. Dual Arterial Cannulation for Acute Type a Aortic Dissection: A Propensity Score Matching Analysis - Chang, Yi; Lin, Hongyuan; Qian, Xiangyang; Guo, Hongwei; Yu, Cuntao; Sun, Xiaogang; Wei, Bo; Ma, Qiong; Wei, Yizhen; Shi, Yi (Frontiers in Cardiovascular Medicine, 2022)
Background The optimal arterial cannulation site for acute aortic dissection repair is unclear, especially for complex arch surgery. Axillary artery cannulation is widely accepted but adding femoral artery cannulation to it was considered to potentially improve perfusion and early outcomes. To clarify this point, a comparison of perioperative outcomes for these two different cannulation strategies was conducted regarding the pathological features of dissection. Methods From January 2010 to December 2019, 927 consecutive patients underwent a total arch replacement combined with frozen elephant trunk for acute type A aortic dissection. The data, including detailed pathological features, were retrospectively collected and analyzed. Propensity score matching and multivariate logistic regression analysis were used for adjusting confounders that are potentially related to the outcome. Results A total of 523 patients (56.3%) accepted a dual arterial cannulation (DAC group), and 406 patients (43.7%) received a single axillary artery cannulation (SAC group). In total, 388 pairs of patients were well-matched. Whether before or after adjusting the preoperative characteristics by matching, there were no significant differences in operative mortality (6.7 vs. 5.4%, P = 0.420 before matching; 5.4 vs. 5.4%, P = 1 after matching), stroke (6.7 vs. 5.4%, P = 0.420 before matching; 6.4 vs. 5.2%, P = 0.435 after matching), spinal cord injury (5 vs. 5.7%, P = 0.640 before matching; 5.4 vs. 5.7%, P = 1. After matching), and acute renal failure requiring dialysis (13.8 vs. 9.6%, P =0.050 before matching; 12.6 vs. 9.5%, P = 0.174) between the two groups. Dual arterial cannulation was not an independent protective factor of operative mortality (odds ratio [OR] 1.01, 95% confidence interval [CI] 0.55–1.86), stroke (OR 1.17, 95% CI 0.65–2.11), spinal cord injury (OR 1.17, 95% CI 0.65–2.11), and acute renal failure requiring continuous renal replacement therapy (CRRT) (OR 1.24, 95% CI 0.78–1.97) after adjusting for confounding factors by multivariable logistic regression analysis. In the subgroup analysis, no advantage of dual arterial cannulation was found for a particular population. Conclusions Single axillary artery cannulation was competent in the complex arch repair for acute aortic dissection, presenting with a satisfactory result as dual arterial cannulation. Adding femoral artery cannulation was necessary when a sufficient flow volume could not be achieved by axillary artery cannulation or when a lower limb malperfusion existed.